The Influence of Product Quality, Price Perception, and Worth of Mouth on Interest to Buy Batik at Batik Nusantara Shops Tanah Abang - Nur Hidayat Fanesa; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of product quality, price perception, and word of mouth on the repurchase intention of batik at the Tanah Abang archipelago batik shop. The data collection method used was by giving questionnaires to 100 respondents using Indonesian batik products, the sample technique using glueshow and the data analysis technique using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) version 23 program. The results of this study indicate that there is a positive and significant influence between the variables of product quality, price perceptions, word of mouth on the intention to repurchase Indonesian batik.